Characterization of biofilms developed from alginate extracted from Padina sp. incorporated with calcium chloride (CaCl2) - E L Hanry; N F M Redzwan; N F A K Badeges; Noumie @ Loumie Surugau (IOP Publishing Ltd., 2022)
Seaweed has been used in many industries, whether directly or its extract. Padina sp. is one of the understudied species of brown seaweed. Brown seaweed have alginate embedded in their cell wall which is a type of hydrocolloids and can be used in many industries and applications including development of biofilms. The main objective of this current study is to develop biofilms using alginate extracted from Padina sp. and incorporated with calcium chloride at different concentrations. Prior to that, the functional groups of Padina sp. and alginate extract were determined. Then, functional groups, surface morphology, mechanical properties, swelling ability and biodegradability of the biofilms were studied using standard methods. The results showed that there were no significant changes in their FTIR spectra with increasing CaCl2 content. Surface morphology showed improvement in bonding while mechanical properties showed the best tensile strength of 9.43mm and 8.61mm elongation-at-break (EAB) after addition of 0.12g CaCl2. As for their swelling and biodegradability, the samples were completely dissolved after one hour and degraded after 24 hours. This shows that the biofilms with CaCl2 indeed improve the quality of alginate-based biofilms which can further be studied to improve other aspects such as water sorption kinetic and thermal stability.